(Rose Bengal)/(Eosin Yellow)-Gold-Polypyrrole Hybrids: A Design for Dual Photo-Active Nano-System with Ultra-High Loading Capacity - El-Kholy AI; Abdel Fadeel D; Nasr M; Fadel M; El-Sherbiny I (Dove Medical Press, 2021)
Abdullah I El-Kholy,1 Doaa Abdel Fadeel,1 Maha Nasr,2 Ibrahim El-Sherbiny,3 Maha Fadel1 1Department of Medical Applications of Laser, Pharmaceutical Nano-Technology Unit, National Institute of Laser Enhanced Sciences (NILES), Cairo University, Giza, Egypt; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Ain Shams University, Cairo, Egypt; 3Nanomaterials Lab, Center for Materials Science, Zewail City of Science and Technology, 6th October City, Giza, EgyptCorrespondence: Maha Fadel Tel +20 1001649550Fax +20 35729499Email mahafmali@niles.edu.egPurpose: Enhancement of the photodynamic/photothermal efficiency of two water-soluble dyes, rose bengal (RB) and eosin yellow (EY), via conjugation to a polymeric nano-system gold-polypyrrole nanoparticle (AuPpy NPs).Methodology: A multi-step synthesis method and an in situ one-pot synthesis method were used. Loading percentage, particle size, zeta potential, morphology, UV-Vis-NIR spectrophotometry and in vitro photothermal activity were measured. Then, both hybrid nanocomposites were examined for their cytotoxicity and photocytotoxicity on HepG2 cell line as a model for cancer cells.Results: Dyes loaded in the traditional multi-step method did not exceed 9% w/w, while in the one-pot synthesis method they reached ∼ 67% w/w and ∼ 75% w/w for EY-AuPpy NPs and RB-AuPpy NPs, respectively. UV-Vis-NIR spectrophotometry showed that both nano-systems exhibited intense absorption in the NIR region. The mean size of the nanoparticles was ∼ 31.5 nm (RB-AuPpy NPs) and ∼ 33.6 nm (EY-AuPpy NPs) with zeta potential values of − 26.5 mV and − 33 mV, respectively. TEM imaging revealed the morphology of both hybrids, showing ultra-nano spherical-shaped gold cores in the case of RB-AuPpy NPs, and different shapes of larger gold cores in the case of EY-AuPpy NPs, both embedded in the polymer film. Conjugation to AuPpy was found to significantly reduce the dark cytotoxicity of both RB and EY, preserving the photocytotoxicity of EY and enhancing the photocytotoxicity of RB.Conclusion: Gold-polypyrrole nanoparticles represent an effective delivery system to improve the photodynamic and photothermal properties of RB and EY. The in situ one-pot synthesis method provided a means to greatly increase the loading capacity of AuPpy NPs. While both hybrid nanocomposites exhibited greatly diminished dark cytotoxicity, RB-AuPpy NPs showed significantly enhanced photocytotoxicity compared to the free dyes. This pattern enables the safe use of both dyes in high concentrations with sustained action, reducing dose frequency and side effects.Keywords: polypyrrole nanoparticles, polymerization, nano-system, photosensitizer, photocytotoxicity